An investigation into ultrasonic waves in distance measurement - Mohamed Raqeeb Mohamed Hamzah Caffoor. (2010)
This study looks at the investigation into the distance measurement of ultrasonic waves. The purpose of the study is to determine a possible achievement of an accuracy of ±1 mm for a 40 kHz ultrasonic transducer in measuring distance through a series of controlled experiments with varying parameters. A comparison was done between the different forms of distance measuring devices to identify the advantages and disadvantages of Ultrasonic Distance Measuring Devices (UDMDs) against other distance measuring devices. Also, a comparison was done between available devices in the market to find out the accuracies and features specified on the devices.